Invitation ? RMCMI 1998 -1999 Board of Directors (Rocky Mountain Coal Mining Institute, 1998)
CLARK MOSELEY RMCMI PRESIDENT 1998-1999 on behalf of the RMCMI Board of Directors and Officers of The Rocky Mountain Coal Mining Institute cordially invites you and your family to attend the 95th Regular Meeting and Convention to be held June 27 thru June 29, 1999 Crested Butte, Colorado